The study on information system planning satisfaction in structured IT/IS management: the Malaysian public sector perspective / Mohd Akmal Mohd Azmer - Mohd Azmer, Mohd Akmal (2011)
The present quantitative study examined the satisfaction on information system planning as a continuance determinant from Malaysian Public Sector Perspective. The study is proposed to explain the perception on the information system planning by the user in pre and post adoption of the information system plan. The adoption of expectation confirmation model is incorporated in the study to explain the relationship within the determinants. The quantitative study produced a plausible conclusion on the findings made from the study through numerical justification. A total of 100 questionnaire distributed to a known population of Malaysian Public sector agencies. The data is analysed using the Pearson Correlation Test to establish the relationship between the determinants. In order to explain the relationship with accordance to the continuance model, multiple regressions is applied in the data analysis. The findings indicate that all variable studied have a positive relationship. The variables studied are perceived usefulness, confirmation, satisfaction, and continuance. The study on the satisfaction of information system planning could provide a numerical rationalization to the importance of user perception on the information system planning.